Toward productivity in future construction: mapping knowledge and finding insights for achieving successful offsite construction projects. Issue 1 (6th November 2020) - Jang, Junyoung; Ahn, Seungjun; Cha, Seung Hyun; Cho, Kyeongwoon; Koo, Choongwan; Kim, Tae Wan
Abstract: Although offsite construction (OSC) has emerged as a promising solution to low productivity issues in the construction industry, knowledge for effective management of OSC projects is yet to be explored and developed further. To enhance our understanding of the landscape of the current OSC management knowledge, this study identified and reviewed 83 operation-level OSC management papers. By mapping the papers on three dimensions (i.e. OSC project type, project phase, and management area), this review sheds light on the knowledge areas addressed more frequently than the other areas over time in a detailed manner. The review also shows that papers on planning, manufacturing, maintenance phases and schedule, resources, and stakeholder management areas have a relatively large number of citations, implying a great interest in these research areas. Finally, the review discusses that substantial research work is still required in the areas of OSC execution strategy, emerging technologies in offsite manufacturing and schedule management, internet of things (IoT)-based material logistics planning and tracking, building information model-based visualization and decision support, and social and environmental effects of stakeholder engagement in OSC projects. Graphical Abstract: